2014
DOI: 10.1002/term.1906
|View full text |Cite
|
Sign up to set email alerts
|

Poloxamine/fibrin hybrid hydrogels for non-viral gene delivery

Abstract: Hydrogels have been widely investigated for localized, sustained gene delivery because of the similarity of their physical properties to native extracellular matrix and their ability to be formed under mild conditions amenable to the incorporation of bioactive molecules. The objective of this study was to develop bioactive hydrogels composed of macromolecules capable of enhancing the efficiency of non-viral vectors. Hybrid hydrogels were prepared by simultaneous enzymatic and Michael-type addition crosslinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Tissue compliance has also been shown to play an important role in DNA uptake and expression. Multiple studies have shown that plasmids transfected into cells plated on a soft substrate express protein more efficiently than on a stiffer substrate [53,54,55]. Studies reported earlier showed that hydrogels of Elastic modulus of 10 kPa…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue compliance has also been shown to play an important role in DNA uptake and expression. Multiple studies have shown that plasmids transfected into cells plated on a soft substrate express protein more efficiently than on a stiffer substrate [53,54,55]. Studies reported earlier showed that hydrogels of Elastic modulus of 10 kPa…”
Section: Discussionmentioning
confidence: 99%
“…ECM protein crosslinking and stiffening leads to progression of tumors in breast cancer via integrin signaling [52]. The transfection efficiency of polyplexes is highly enhanced by matrix stiffness [53,54,55].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 The more well-known linear counterparts of Tetronics -Pluronicare currently undergoing clinical trials with the cancer drug doxorubicin 7 and the recent demonstration of the ability of Tetronics to also inhibit ATP-binding cassette transporters in cancer cell lines, responsible for multidrug resistance, 5 added to their pH-responsiveness, has recently brought them into the spotlight as serious contenders in the biomedical field. 6 Indeed, they have been proposed as water-soluble copolymers for injectable formulations, 8 nanocarriers for drug and gene delivery 9,10 and in tissue engineering for bone regeneration. 11 The introduction of different types of nanoparticles into hydrogels is a successful way to not only improve existing characteristics (such as gel elasticity and toughness), but also add extra functionalities to the hydrogels, [12][13][14] resulting in new, functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…Gene therapy offers the potential to stimulate tissue regeneration and treat disease through the overexpression or silencing of target genes, including cancer and infection [77,78] . Therefore, it is of great significance to combine the genetic agents with appropriate material in a definite and reversible way.…”
Section: Gene Deliverymentioning
confidence: 99%